Studi kasus evaluasi penaatan aspek pengolahan limbah cair industri farmasi - Sasanti Meirdana; Suyud Warno Utomo (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2020)
Pharmaceutical industry is one of the industries experiencing growth in Indonesia. One of the pharmaceutical companies in Indonesia is PT X. In its production activities, company produces four groups of waste, namely liquid, domestic, hazardous (B3) and gas waste. The aim of this research was to evaluate the effectivity of liquid waste management system and the compliance of liquid waste management towards regulatory provisions in Indonesia. The research method applied descriptive qualitative approach. Data collection including documentation, observation and unstructured interviews. Treatment of domestic, production and supporting activities waste using anaerobic-aerobic method with the proportion of 70:30. Waste treatment activities results revealed that the trend of parameters always met the existing quality standards for the last 3 years, except COD.